ANALISIS PERILAKU HERDING DAN OVERCONFIDENCE DALAM PENGAMBILAN KEPUTUSAN INVESTASI GENERASI Z KABUPATEN JOMBANG DI PASAR SAHAM SYARIAH INDONESIA - Beni Sucipto; Saiful Aminudin Al Kusuma Putra; Nurianah; Irea Arrahima (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2026)
This study examines the effects of herding behavior and overconfidence on investment decision-making among Generation Z in Jombang Regency in the Islamic (Sharia-compliant) stock market. The study is motivated by the growing interest in investing among young people, supported by financial technology, yet accompanied by vulnerability to behavioral biases that may affect the rationality of decisions. This research adopts a quantitative approach using a survey of 150 Generation Z investors in Jombang who actively invest in Sharia-compliant stocks. The data were analyzed using multiple linear regression. The data analysis technique employed was PLS-SEM, and the analytical tool used was SmartPLS version 4. The results show that herding has no significant effect on investment decision-making, whereas overconfidence has a significant effect and is the most dominant factor. This indicates that Generation Z in Jombang does not tend to directly follow others’ behavior or external recommendations when making investment decisions. Instead, they are more influenced by a high level of self-confidence in their own ability to analyze market information. These findings suggest that Generation Z’s investment decisions in Jombang are highly rational. This study recommends strengthening Islamic financial literacy education to develop smarter and more mature investors.